Surface Character of Magnetic Ce-doped TiO2 for Photocatalytic Performance Enhancement - Tia Rahmiati; Ching-Cheng Chen; Siti Asmahani Saad; Nugroho Eko; Asep Apriana (Recent in Engineering Science and Technology, 2023)
Using a modified sol-gel method for magnetic photocatalyst, the core shell structure of Ce-doped TiO2@SiO2@ferrite composite nanoparticles (NPs) was created. X-ray diffraction (XRD), Brunauer–Emmit–Teller (BET), and a superconducting quantum interference device (SQUID) were used to examine the physicochemical properties of the products as they were prepared. The ultraviolet-visible spectrometry (UV-vis) was used to measure the catalyst's photocatalytic activity. On the composite NPs' outer shell coating, the anatase phase related to the TiO2 structure was constructed. On the Ce-doped TiO2 layers, a mesoporous structure with uniform pore size was created, resulting in a specific surface area of 111.916 m2g-1. In the meantime, the thin TiO2 coating contained the redox couple of Ce3+ and Ce4+. An external magnetic field can also be used to separate the catalyst's magnetic NPs from the reaction system. In the aqueous solution of methylene blue (MB), the degradation efficiency and product performance were both 50 percentage